2018
DOI: 10.4236/ce.2018.92016
|View full text |Cite
|
Sign up to set email alerts
|

School Psychology on the Formation of the Social Educator: Assessment of the Professional Profile

Abstract: In Brazilian scenario, the profession of the social educator is recent in the non-formal educative spaces, including institutions which act in benefit of the poorest segments of the population. With the intent to contribute to the discussion on the formation of the social educator, this manuscript seeks to investigate the professional profile resources of social educators from a Brazilian Non-Governmental Organization (NGO) and the possibilities of contribution from the School and Educational Psychology to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The results of the previous international studies ( GALVÃO et al, 2018) have indicated that the transversal competencies (interpersonal, ethical, and esthetical resources) are better developed than technical competences (theoretical-conceptual and technical and scientific resources), which are related to initial and continuous social educator's formation. Also, future social educators most valued regular supervision, constructive feedback, observing social workers, and thinking critically about the social work role (ROULSTON et al, 2018).…”
Section: Discussion and Conclussionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the previous international studies ( GALVÃO et al, 2018) have indicated that the transversal competencies (interpersonal, ethical, and esthetical resources) are better developed than technical competences (theoretical-conceptual and technical and scientific resources), which are related to initial and continuous social educator's formation. Also, future social educators most valued regular supervision, constructive feedback, observing social workers, and thinking critically about the social work role (ROULSTON et al, 2018).…”
Section: Discussion and Conclussionsmentioning
confidence: 99%
“…Based on the hierarchy model of research competence development (Galvão et al 2018;Higgins 2015a) we have described the formation of research competence by three levels: initial, service, advanced.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations